Stigmas and Petals of Crocus sativus L. (Taliouine, Morocco): Comparative Evaluation of Their Phenolic Compounds, Antioxidant, and Antibacterial Activities - Asmaa Benkerroum; Khadija Oubella; Soukaina Zini; Kaoutar Boussif; Hind Mouhanni; Fouad Achemchem (The Scientific World Journal)
The dried stigmas of Crocus sativus L. produce saffron, a precious spice used for its culinary and medicinal properties since ancient times, while its petals are considered the main by-product of saffron production. The present study aimed to comparatively evaluate the phenolic content, antioxidant capacity, and antibacterial activity of methanolic extracts of stigmas and petals of Crocus sativus L. from Taliouine. The polyphenol content was measured using the Folin–Ciocalteu method, the antioxidant activity was determined using the DPPH free radical scavenging method, and the well-diffusion method was used to assess antibacterial activity against seven pathogenic bacterial strains (Bacillus subtilis, Escherichia coli, Listeria monocytogenes, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella enterica, and Staphylococcus aureus). Furthermore, the minimum inhibitory concentration (MIC) of the extracts was determined using the microdilution broth test. Our findings revealed that stigmas and petals contained phenolic compounds at the rate of 56.11 ± 4.70 and 64.73 ± 3.42 mg GAE/g, as well as DPPH radical scavenging capacity with IC50 of 1700 µg/ml and 430 µg/ml, respectively. Petal extract showed more effective antibacterial activity, with inhibition diameters ranging from 10.66 ± 0.57 to 22.00 ± 1.00 mm and MIC values ranging from 2.81 to 5.62 mg/ml, compared to the stigma extract, which displayed inhibition diameters from 10.00 ± 0.00 to 18.67 ± 0.76 mm and MIC from 2.81 to 11.25 mg/ml, against five of the seven bacterial strains tested, including S. aureus, E. coli, P. vulgaris, P. aeruginosa, and S. enterica. Statistical analyses were performed to determine the significance of these results. Thus, stigmas and petals of Crocus sativus L. might serve as a suitable source of natural antioxidant and antimicrobial agents for application in the food and pharmaceutical industries.